2020
DOI: 10.21203/rs.3.rs-53542/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Host and Geographical Regions on the Rumen Methanogens Diversity in Indian Cattle and Buffaloes

Abstract: Background Archaea belong to the domain Euryarchaeota, represents only 3-5% of the rumen microbiota; however, they play a central role in maintaining the H2 pressure. Host species in conjunction with geographical regions may lead to the variable distribution of rumen methanogens. Indian cattle and buffaloes represent 13 and 53% of the global population, respectively. However, the influence of host species (bovine) and geographical regions on the methanogens distribution has not been investigated in Indian subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…A meta-analysis [ 65 ], concluded that the methanogens associated with the genus Methanobrevibacter are similarly distributed in cattle and buffaloes. Further, similar distributions of Methanobrevibacter in Indian cattle and buffaloes belonging to two distinct geographical regions were reported in a recent study by Trivedi et al [ 55 ]. The above studies reporting the similar proportion of Methanobrevibacter were either conducted separately in cattle and buffaloes or both the species were fed on different diets or having uncontrolled environmental conditions prevailing in different geographical regions; hence, these previous studies did not reveal the actual impact of the hosts on the proportion of ruminal methanogens.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A meta-analysis [ 65 ], concluded that the methanogens associated with the genus Methanobrevibacter are similarly distributed in cattle and buffaloes. Further, similar distributions of Methanobrevibacter in Indian cattle and buffaloes belonging to two distinct geographical regions were reported in a recent study by Trivedi et al [ 55 ]. The above studies reporting the similar proportion of Methanobrevibacter were either conducted separately in cattle and buffaloes or both the species were fed on different diets or having uncontrolled environmental conditions prevailing in different geographical regions; hence, these previous studies did not reveal the actual impact of the hosts on the proportion of ruminal methanogens.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, Group 8 methylotrophs were exclusively identified in the cattle. The greater proportion of Group 8 methanogens in cattle compared to their distribution in buffaloes has recently been confirmed [ 55 ]. This difference should be taken into account while developing strategies for methane mitigation from cattle and buffaloes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another recent report from Seshadri et al (2018) showed that hydrogenotrophic methanogens accounted for 78% of ruminal methanogens, whereas methylotrophic methanogens accounted for the remaining 22%. A comparison of methanogens inhabiting the rumen of water buffaloes and cattle (Trivedi et al, 2020) showed differences in the relative abundance of individual methanogens, although similar methanogens (diversity) were observed as described in previous reports. Methanobrevibacter gottschalkii was predominant in the rumen of water buffaloes (30-55%) followed by Methanobrevibacter ruminantium (5-10%) and Methanosphaera ISO3-F5 (2-5%), although regional differences were noted in the relative abundance of individual populations among water buffaloes.…”
Section: Global Efforts Needed To Understand Methanogen Diversitysupporting
confidence: 84%